Main nutrients and functional ingredients in flowers of Polygonatum cyrtonema and P. filipes - Zhang, Ze-Rui; Huang, Shen; Liu, Jing-Jing; Zhang, Xin-Feng; Si, Jin-Ping (Zhongguo zhongyao zazhi, 2020)
To reveal the main nutrients and functional ingredients in the flowers of Polygonatum cyrtonema and P. filipes, the content of the polysaccharides, saponins, amino acids, total phenols, mineral elements, and the DPPH free radical scavenging rates were determined. The flowers and rhizomes of P. cyrtonema were collected from Qingyang in Anhui and Qingyuan in Zhejiang, while the flowers and rhizomes of P. filipes were collected from Longyou in Zhejiang, respectively. The results showed that the polysaccharides content in flowers varied from 60.88 to 97.00 mg·g~(-1), about half of that in rhizomes. The saponins content in flowers varied from 32.55 to 40.93 mg·g~(-1), which was close to the content in rhizomes. The content of total phenols ranged from 40.79 to 50.95 mg·g~(-1), approximately 4.5 times of that in rhizomes. The total amino acids content in flowers was 111.85 to 131.03 mg·g~(-1), about 2.3 times of the content in rhizomes. The essential trace element content was abundant in flowers. The contents of he